Effects of bile acid sequestration on hepatic steatosis in obese mice - Solís, Nancy (2014)
Background: Bile acid sequestration (BAS) with resins has shown antidiabetic effects in both humans and animals. Since hepatic steatosis is commonly associated to type 2 diabetes mellitus and the effects of BAS on steatosis have not been explored in detail, we evaluated the effects of cholestyramine (CTM) administration on fatty liver development in the leptin-deficient obese mice. Aim: To study the effects of BAS on fatty liver development in obese mice. Methods: 4 week-old ob/ob mice (B6.V-Lepob/J, n=4-6 per group) were fed with CTM during 8 weeks. Serum and biliary parameters, glucose tolerance test (GTT), hepatic triglyceride content, liver histology and hepatic gene expression of relevant genes related to bile secretion, lipid and glucose metabolism were assessed. Results: 12-week-old mice exhibited marked obesity and hepatic steatosis. CTM administration expectedly determined a marked de-repression of 7-alpha-hydroxylase and decreased biliary bile acid secretion as well as improved GTT. CTM feeding showed no effects on hepatic triglyceride content or in the degree of steatosis on liver histology. CTM was associated to increased levels of serum alanine-aminotransferase. Conclusion: Although CTM administration positively affects glucose tolerance it does not prevent hepatic steatosis development in obese mice. Moreover, CTM feeding was associated to liver enzyme elevation in this model of NAFLD. Thus, the effects BAS on NAFLD need to be specifically addressed since this therapy might not be beneficial for NAFLD.